Effect of circular RNA, mmu_circ_0000296, on neuronal apoptosis in chronic cerebral ischaemia via the miR-194-5p/Runx3/Sirt1 axis - Huang, Keyu (Cell Death Discov, 2021)
Chronic cerebral ischaemia (CCI) is a common pathological disorder, which is associated with various diseases, such as cerebral arteriosclerosis and vascular dementia, resulting in neurological dysfunction. As a type of non-coding RNA, circular RNA is involved in regulating the occurrence and development of diseases, such as ischaemic brain injury. Here, we found that HT22 cells and hippocampus treated with CCI had low expression of circ_0000296, Runx3, Sirt1, but high expression of miR-194-5p. Overexpression of circ_0000296, Runx3, Sirt1, and silenced miR-194-5p significantly inhibited neuronal apoptosis induced by CCI. This study demonstrated that circ_0000296 specifically bound to miR-194-5p; miR-194-5p bound to the 3′UTR region of Runx3 mRNA; Runx3 directly bound to the promoter region of Sirt1, enhancing its transcriptional activity. Overexpression of circ_0000296 by miR-194-5p reduced the negative regulatory effect of miR-194-5p on Runx3, promoted the transcriptional effect of Runx3 on Sirt1, and inhibited neuronal apoptosis induced by CCI. mmu_circ_0000296 plays an important role in regulating neuronal apoptosis induced by CCI through miR-194-5p/Runx3/Sirt1 pathway.